“I can’t imagine having to do it on your own”: a qualitative study on postoperative transitions in care from the perspectives of older adults with frailty - Hladkowicz, Emily; Auais, Mohammad; Kidd, Gurlavine; McIsaac, Daniel I.; Miller, Jordan (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Adults aged 65 and older have surgery more often than younger people and often live with frailty. The postoperative transition in care from hospital to home after surgey is a challenging time for older adults with frailty as they often experience negative outcomes. Improving postoperative transitions in care for older adults with frailty is a priority. However, little knowledge from the perspective of older adults with frailty is available to support meaningful improvements in postoperative transitions in care. Objective To explore what is important to older adults with frailty during a postoperative transition in care. Methods This qualitative study used an interpretive description methodology. Twelve adults aged ≥ 65 years with frailty (Clinical Frailty Scale score ≥ 4) who had an inpatient elective surgery and could speak in English participated in a telephone-based, semi-structured interview. Audio files were transcribed and analyzed using thematic analysis. Results Five themes were constructed: 1) valuing going home after surgery; 2) feeling empowered through knowledge and resources; 3) focusing on medical and functional recovery; 4) informal caregivers and family members play multiple integral roles; and 5) feeling supported by healthcare providers through continuity of care. Each theme had 3 sub-themes. Conclusion Future programs should focus on supporting patients to return home by empowering patients with resources and clear communication, ensuring continuity of care, creating access to homecare and virtual support, focusing on functional and medical recovery, and recognizing the invaluable role of informal caregivers.